PACAP/Receptor System in Urinary Bladder Dysfunction and Pelvic Pain Following Urinary Bladder Inflammation or Stress - Girard, Beatrice M.; Tooke, Katharine; Vizzard, Margaret A. (Frontiers in Systems Neuroscience, 2017)
Complex organization of CNS and PNS pathways is necessary for the coordinated and reciprocal functions of the urinary bladder, urethra and urethral sphincters. Injury, inflammation, psychogenic stress or diseases that affect these nerve pathways and target organs can produce lower urinary tract (LUT) dysfunction. Numerous neuropeptide/receptor systems are expressed in the neural pathways of the LUT and non-neural components of the LUT (e.g., urothelium) also express peptides. One such neuropeptide receptor system, pituitary adenylate cyclase-activating polypeptide (PACAP; Adcyap1) and its cognate receptor, PAC1 (Adcyap1r1), have tissue-specific distributions in the LUT. Mice with a genetic deletion of PACAP exhibit bladder dysfunction and altered somatic sensation. PACAP and associated receptors are expressed in the LUT and exhibit neuroplastic changes with neural injury, inflammation, and diseases of the LUT as well as psychogenic stress. Blockade of the PACAP/PAC1 receptor system reduces voiding frequency in preclinical animal models and transgenic mouse models that mirror some clinical symptoms of bladder dysfunction. A change in the balance of the expression and resulting function of the PACAP/receptor system in CNS and PNS bladder reflex pathways may underlie LUT dysfunction including symptoms of urinary urgency, increased voiding frequency, and visceral pain. The PACAP/receptor system in micturition pathways may represent a potential target for therapeutic intervention to reduce LUT dysfunction.